Bridging scales and borders on water availability and use in the transboundary Volta River Basin: A water accounting approach - Afua Owusu; Komlavi Akpoti; Mansoor Leh; Tharindu Perera; Lahiru Madushanka; Kirubel Mekonnen; Primrose Tinonetsana; Noosha Tayebi; Ana Cecilia Escalera-Rodriguez; Rafatou Fofana; Naga Manohar Velpuri (Journal of Hydrology: Regional Studies)
Study region: Volta Basin Study focus: Water management in transboundary basins is challenging due to the interaction of natural and human factors across political borders. The Volta River Basin, shared by six West African countries, exemplifies this with variable water distribution and socio-economic pressures. This study presents a comprehensive multi-scale water accounting of the basin, assessing water flows and usage at basin-wide, sub-basin, and riparian country scales from 2003 to 2021. New hydrological insights for the region: The results reveal average basin closure is 55 % with room for additional water allocation given that utilizable water in the basin is 20 km3/year and almost 25 % of the basin’s exploitable water is non-recoverable water (wastewater). Sub-basin analysis showed variations in average annual rainfall, ranging from 940 to 1250 mm/year, and groundwater recharge rates (18–64 mm/year), with southern sub-basins receiving more rainfall and having higher recharge rates. Similarly at the country level, variability in rainfall (630–1220 mm/year) and recharge rates (20–280 mm/year) were noted, with downstream countries benefiting from higher rainfall and significant inflows from upstream countries. The analysis underscored the interconnectedness of water use across the basin's riparian countries. The study's findings give insights for the strategic management of water resources and the crucial need for enhanced cooperation among riparian countries to address shared challenges and opportunities in the Volta Basin.